1990
DOI: 10.1213/00000539-199004000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Infusion of Nitroglycerin and Nicardipine on Femoral-to-Radial Arterial Pressure Gradient After Cardiopulmonary Bypass

Abstract: Nitrates and calcium channel blockers are frequently administered during cardiac surgery. We simultaneously measured femoral arterial pressure and radial arterial pressure to investigate whether nitrates, in conjunction with calcium channel blockers, would influence the central-to-peripheral arterial pressure gradient. Combined nitroglycerin and nicardipine infusion during cardiac surgery involving coronary artery bypass grafting or valve replacement resulted in a significant increase above baseline levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…Interestingly, several studies from the 1980s suggested that vasodilatory agents might intensify PD. 10,12 Maruyama et al 16 reported that the use of vasodilating agents such as nitroglycerin and calcium channel blockers could promote PD. The authors of these studies suggested that a decrease in peripheral vascular resistance could cause a loss of arterial wave reflection and blunting of the arterial pressure wave resulting in underestimation of radial artery pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies from the 1980s suggested that vasodilatory agents might intensify PD. 10,12 Maruyama et al 16 reported that the use of vasodilating agents such as nitroglycerin and calcium channel blockers could promote PD. The authors of these studies suggested that a decrease in peripheral vascular resistance could cause a loss of arterial wave reflection and blunting of the arterial pressure wave resulting in underestimation of radial artery pressure.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that sodium nitroprusside, droperidol, ketanserin and phenylephrine did not affect the magnitude and duration of the pressure gradient during cardiopulmonary bypass (18). On the contrary, according to Maruyama et al., continuous infusion of nitroglycerine and nicardipine intensified the pressure gradient after cardiopulmonary bypass (19). Hynson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Since its first description by Stern and colleagues in 1985, 23 numerous studies have suggested various explanations. Changes in distal arterial elasticity, 29 aging with a reduction in leg postjunctional alpha-adrenoceptor responsiveness to endogenous noradrenaline, 30 lower hematocrit level, 7 lower minimal body temperature, 8 CPB and clamping times, 1 , 2 vasoactive medication, 1 , 2 , 9 , 10 , 31 , 32 plasma catecholamine levels, 9 , 10 vascular thrombosis, 33 vascular decoupling in vasoplegia, 34 and demographic data 1 , 2 have all been described as potential risk factors. There is also a discrepancy in regard to vasoactive medication, since vasopressors and vasodilators have both been associated with the RFPG in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a discrepancy in regard to vasoactive medication, since vasopressors and vasodilators have both been associated with the RFPG in different studies. 9 , 28 , 31 , 32 , 35 Although none of these risk factors can explain the phenomenon by itself, most of them are related to vasoconstriction and thus to radial artery diameter. Our observations support the concept that a smaller preoperative radial artery diameter can affect pulse pressure and thereby generate an abnormally low reduction in radial arterial pressure compared with central or femoral arterial pressures.…”
Section: Discussionmentioning
confidence: 99%